2003
DOI: 10.1111/j.1600-0765.2004.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of centrifugal force on mRNA levels of collagenase, collagen type‐I, tissue inhibitors of metalloproteinases and β‐actin in cultured human periodontal ligament fibroblasts

Abstract: The results indicate that PDL remodeling following application of orthodontic force could be partly attributed to the direct effect of the force on MMP-1 gene expression in fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 27 publications
(33 reference statements)
2
36
1
10
Order By: Relevance
“…where P = kg pressure per cm 2 of cells, m = mass of medium (0.002 kg), r = radius (0.09 m), rpm = revolution /min (600 or 4,800) and A = area of contact between medium and cells (9.62 cm 2 ) (20)(21)(22)(23). The cells on the dishes were then cultured continuously up to 7 days.…”
Section: Procedures Of Treating Cells With Centrifugal Forcementioning
confidence: 99%
“…where P = kg pressure per cm 2 of cells, m = mass of medium (0.002 kg), r = radius (0.09 m), rpm = revolution /min (600 or 4,800) and A = area of contact between medium and cells (9.62 cm 2 ) (20)(21)(22)(23). The cells on the dishes were then cultured continuously up to 7 days.…”
Section: Procedures Of Treating Cells With Centrifugal Forcementioning
confidence: 99%
“…However, the expression patterns of these molecules in response differed according to the modes of the mechanical stress, such as shear, compression, and tension as well as the magnitudes of the stress (Redlich et al, 2004;Ozaki et al, 2005;Garlet et al, 2007;Kook et al, 2009). Previous evidence has shown that cyclic tensile stress (CTS) during orthodontic tooth movement (OTM) increases the expression of osteogenic genes and proteins such as alkaline phosphatase (ALP), secreted phosphoprotein 1 (SPP1; also known as bone sialoprotein I/osteopontin), transcription factor Sp7 (SP7; also known as osterix), and runt-related transcription factor 2 (RUNX2) of hPDLCs (Wescott et al, 2007;Cho et al, 2010;Tang et al, 2012).…”
mentioning
confidence: 99%
“…We reported that continuous force induced morphological changes of cultured osteoblasts and possibly affected the autocrine structural pathway that might link the nucleus to the mechanotransduction and accelerate the expression of the c-fos gene in the nucleus (30). OPN has been recognized as a regulator of responses to mechanical stress (21,26,37). Toma et al demonstrated that OPN produced by osteoblasts plays a role in the mechanosignal transduction, and this possibly depends on a protein kinase A-like kinase (36).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of various types of mechanical stress, such as centrifugal force (23)(24)(25)(26)(27), stretching force (11,17,20,(28)(29), compressive force (30) and shear stress (18) on cells have been reported. An advantage of using centrifugal force in vitro is that it is possible to add even amounts to cells without changing the culture conditions, such as decreasing the oxygen or depleting the nourishment.…”
Section: Discussionmentioning
confidence: 99%